Sculptural Formation in the Third Millennium: Styles and Trends (Al-Academy, 2018)
The research studies the sculptural formation in the third millennium: styles and trends, by taking the most important results of sculpture in the third millennium. The problem of the research is to search for the new sculptural formation in what it constitutes of social and human importance, and what are the important factors in forming the contemporary sculptural structure, and what is the mechanism of showing and producing the new formation. The research requires the study of the most important thing that the (sculptural formation in the third millennium styles and trends) represents. The importance of research depends on the importance of the sculptural formation after the twentieth century and the importance that the form represents in the intellectual discourse in the third millennium of diversity and formation. The aim of the research is to reveal the sculptural formation in the third millennium.The current research may be delimited to studying the sculptural works carried out of all modern materials after the twentieth century, i.e., (2000-2018) in Europe and America. The research also defined the terms used. The study consists of two sections: the first is the thought and the authority in the modern sculptural formation, while the second section tackles the modern sculptural formation: styles and trends which reviews the most important intellectual, philosophical and formal approaches and the most important postmodern sculpture trends which were a major cause in the new formation. This chapter concluded with the most important indicators that can be used in the research procedures.The methodological framework included the research procedures such as the research community, methodology, models, and the justification for the selection of (4) samples. They have been chosen because they represent the research community and its temporal limitation through which the objective of the research is reached after analyzing them leading to the most important findings, conclusions, recommendations and suggestions presented by the researcher. The results of the research included:The works of the third millennium presented a sculptural structure and a self-orientation that transformed the construction of form and style into a free aesthetic standard and value and into a personality that reflects the imaginative perceptions of the spirit through freedom of expression, as in all models. The works of the sculptors in the third millennium were characterized by a variety of shapes, methods, techniques and presentation methods, through their dealing with the types and shapes of the new sculptural materials that came after their rejection of the traditional raw materials in sculpture, putting for themselves an art special for them as a result of their own personal experiences as in all modelsfindings, conclusions, recommendations and proposals. Then the results of the research and discussed, including The work of the third millennium came in a sculptural structure and self-orientation that referred the construction of form and style to a free and personal aesthetic standard and value that reflected the imaginative perceptions of the spirit through freedom of expression, as in all models The work of the sculptors in the third millennium was characterized by a variety of shapes, methods, techniques and presentation methods, through their dealing with the types and shapes of the new sculptural materials that came after rejecting the traditional raw materials in sculpture, putting their own art as a result of their own experiences and experiences as in all models